2022
DOI: 10.21203/rs.3.rs-1224124/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analysis of Physical and Chemical Properties of Alternative Substrate Material for Sustainable Green Roofs

Abstract: Green roof of a building is partially or completely enfolded with vegetation and its associated components. It promotes the sustainability and comfort of buildings. This study determines the most suitable growing substrate by investigating organic wastes of Sawdust, Wood bark, Bio char, Coir, Compost and Base medium (fertilizer + potting mix) through comparing density, moisture content, drought resistance, thermal resistance, vegetation growth, pH, electric conductivity (EC) and nutrients. Unlike previous stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In addition, high EC (Electrical conductivity) has a negative effect on nutrient uptake such as pH and the productivity of the root zone environment where the plant grows. For this reason, the material that provides the lowest EC (Electrical conductivity) level among filtration materials is important in terms of creating a positive environment for plant growth in roof gardens (Sönmez, 2013;Kader et al, 2022). Therefore, in accordance with the results obtained from the research, it is recommended to use polypropylene fabric (F2) in extensive roof garden arrangements, as it has the lowest salinity value among the filtration materials.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In addition, high EC (Electrical conductivity) has a negative effect on nutrient uptake such as pH and the productivity of the root zone environment where the plant grows. For this reason, the material that provides the lowest EC (Electrical conductivity) level among filtration materials is important in terms of creating a positive environment for plant growth in roof gardens (Sönmez, 2013;Kader et al, 2022). Therefore, in accordance with the results obtained from the research, it is recommended to use polypropylene fabric (F2) in extensive roof garden arrangements, as it has the lowest salinity value among the filtration materials.…”
Section: Discussionmentioning
confidence: 91%
“…Like other qualities, the pH level of the plant's root zone in the roof garden can change. However, it is suggested that the pH should be between 7.0 and 9.0, a range that allows the nutrient absorption of the plants used in roof gardens, and this should be stabilised to ensure the plants' health (Ampim et al, 2010;Kader et al, 2022). When the limit is exceeded, nutrients cannot be absorbed by plants and nutrient deficiency symptoms start being observed; root development, yield and plant quality are adversely affected (Sönmez, 2013;Ding et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The main objective of this subtopic is to study regarding the growing mediums utilised in previous research studies and to know their corresponding mix proportions. Because the best fitting ration would not only enrich the vegetation with nutrients and water seepage (Young, 2014), but also prevent the substrate system from becoming a heavyweight component which is an essential requirement for the longevity of medium rise and high rise buildings (Ahmed and Alibaba, 2016;Khan and Asif, 2017;Mahmoodzadeh et al, 2019;Kader et al, 2021). Table 1 illustrates the details regarding the mix proportions and compositions used for substrate preparations in the past studies.…”
Section: Proportion Of Substrate Compositionsmentioning
confidence: 99%
“…Green roof substrates are categorised into two main types: mineral substrates and organic substrates (Noya et al, 2017). In terms of mineral substrates, the naturally available topsoil, clay, pumice, sand, and gravel are used as substrates for green roofs due to their great ability to retain moisture (Kader, Jaufer, Shiromi, & Asmath, 2021). However, natural mineral-based growing mediums are hefty in weight, causing additional designs on the roof to maintain the structural stability of the structure (Ampim et al, 2010;Zejak et al, 2022).…”
Section: Introductionmentioning
confidence: 99%